Rancangan Undang-Undang Pemberantasan Tindak Pidana Terorisme Dalam Perspektif HAM - Wulansari, Harni Septiana, Muchammad Iksan, SH.MH (2017)
The purpose of this study was to determine the Draft Law Combating Criminal Acts of Terrorism in the perspective of human rights and policies that should be regulated in the draft Law on Combating Criminal Acts of Terrorism in order to protect human rights. In this study the authors use the method of normative legal research (doctrinal) with through legislation approach and conceptual. Results showed that: First, some of the new charge contained in the ftEradication of terrorism contrary to human rights; Second, the authority of the investigators in arresting, detaining and tap the phones need to be strictly limited to prevent abuse of power and human rights violations.